Cenários públicos juvenis: o desenho dos Centros de Juventude nas ações da política brasileira - Barreiro, Rafael Garcia (2014)
The Youth Centers were created from a project of the federal government in the late 1990s in order to function as spaces those offer information and activities in many fields, creating a living space for young. This work, from his affiliation with the Social Occupational Therapy, aimed to understand the consonance between the actions of the Youth Centers with the proposals and guidelines of the National Youth Policy, noting that in recent years, the national public agenda gained strength from the creation of the National Youth Secretariat. To cut this research, it has chosen the state of São Paulo because of your numerical and political representation in the country. To collecting data, the Juventude.SP electronic portal has consulted, bringing official information about the services for young people in the state of São Paulo, where four municipalities were identified with spaces called "Youth Centers", namely: Barretos, Jacarei, Santos and São Carlos. In this universe, semi-structured interviews were made with different political representatives of related to youth policies: one representative of the National Secretariat for Youth, Coordinator of Youth Programs for the State of São Paulo, municipal managers and coordinators of the four Youth Centers; to understand which is established by all political today for this population. The general results on the current youth policy brought a reflection about the discourses obtained at each governmental level, through topics such as: the concepts of youth assigned by managers, the understanding of the actions those are currently performed by different levels government, the relationship of those spaces with cash transfer programs, the definition of "youth leadership" and the goal of the Youth Centers. The distance in the positions of managers stayed evident, depending on the level of action taken by each institutional space. The discourse about the actions the federal and state levels is focused on ensuring the access of specific rights for this population, contrasting the actions performed in the municipalities, pointing their political agenda guided by the social assistance. It is evident that the focus should be designed on the principles of universality and access to rights, but it is still guided primarily in the logic of the cut of social class, targeted to young poor. In this context, the Youth Centers do a little interface with the National Youth Policy, being representative of care actions, through focus policies without unfolding the principles for nationally advertised rights for all young Brazilians.